Ultrasmall Optical Vortex Knots Generated by Spin‐Selective Metasurface Holograms. Issue 10 (28th February 2019) - Wang, Lei; Zhang, Weixuan; Yin, Hongxing; Zhang, Xiangdong
Abstract: Tying isolated vortex knots in complex optical fields has been recently realized using spatial light modulators (SLMs). These traditional devices suffer from low efficiency, narrow bandwidth, and they cannot be integrated to nanophotonic systems. Here, the design and realization of metasurface holograms (MHs) is reported to efficiently generate the optical vortex knots in a broad spectral region. In comparison with conventional optical devices, the thicknesses and pixels of MHs are both in subwavelength scale, and the size of created optical vortex knot can be six orders of magnitude smaller than those produced by SLMs. Such extremely little vortex knots may find widespread applications in templating knotted micro/nano‐structures in photosensitive materials and 3D optical trapping of cold atoms in complex topologies at microscale. In particular, it is found that the spatial position of the generated off‐axis optical vortex knot is able to be symmetrically reversed by just changing the helicity of the incident light. This spin‐selective vortex knot generator can be regarded as a new type of metasurface device for manipulating the topological structure of optical vortex lines, which has potential applications in the field of singular optics. Abstract : Optical vortex knots are created by spin‐selective metasurface holograms in a broad spectral region. The size of the created vortex knot can be six orders of magnitude smaller than those produced by spatial light modulators. This ultrasmall vortex knots generator can be regarded as a new type of metasurface device to realize 3D optical trapping of cold atoms at microscale.